Preparation of surface modified kaolines by silicone hydrophobization - Matějková, Eva; Kalendová, Andréa; Obrdlík, Štěpán (Univerzita Pardubice, 2010)
This work deals with preparation of silanized kaolines for application in organic coatings. Coatings have a crucial task in protection of metal materials against rust. Leafy fillers improve anticorrosive properties (they participate in barrier mechanism), stability in atmospheric influences and adhesion to base plate. Organic silicate substances are able to create hydrophobic layer on a surface of different materials. Hydrophobization reduces a possibility of osmotic blisters creation. Four samples were prepared from four types of silanes (polydimethylsiloxane, methyltrimetoxysilane, aminoalkyl siloxane and aminopropylsilane) and two different kaolines. The following samples were prepared: A- Al6Si2O13 (mullite, S1),B- SiO2 (quartz, S2),C- Al6Si2O13 (mullite,S3),D- SiO2 (quartz, S4). Properties which are important for application in coatings were astimated by means of the following tests: structure identification by X-ray diffraction analysis, determination of the specific mass, oil consumption determination, specific surface area determination, determination of particle size and distribution, determination of the morphology of particles. Determination of methanol (MN) and water (WN) number is very important for evaluating anticorrosion properties of silanized samples in coatings. The prepared pigments have diverse chemical composition and content of structural phase quartz and mullite. The characterization of pigments shows good properties of tested pigments for production of coatings. Mechanical and anticorrosive properties will be investigated.
Keywords: silanized kaolines; organic coatings; silicone hydrophobization